Professional stress and job satisfaction of nurses working in infectious diseases wards during the SARS-CoV-2 pandemic - Katarzyna Tomaszewska; Katarzyna Sopel (Kazimierz Wielki University, 2022)
The SARS-CoV-2 pandemic brings many challenges to the daily work of nurses who put their lives and health at risk for the general public every day. This causes them to be highly stressed at work, causes mental strain, and lowers the level of job satisfaction. The aim of the research was to assess the level of stress and job satisfaction of nurses working in infectious diseases wards. Materials and methods The survey was conducted among 169 nurses in the period from February to April 2022. The study was conducted using the diagnostic survey method, the technique was a questionnaire survey, and the survey tool was a survey questionnaire provided in a Google Form. The differences between the qualitative variables were analyzed using the χ2 test of independence. We use the χ2 test of independence (non-parametric significance test for two or more independent samples) to test whether the variables measured at the nominal level or higher in the comparison groups differ from each other. The significance level of the study was p <0.05. The calculations were made with the SPSS 25 software. Results Work in direct contact with people infected with the coronavirus was performed by the majority of the respondents. Only about 18.0% of nurses used psychological assistance during the pandemic. Among the harmful and nuisance factors in the workplace, the respondents mentioned stress, contact with potentially infectious material, coronavirus infection despite appropriate personal protective equipment and cuts. Conclusions Stress in the workplace was felt especially due to the need to operate specialized equipment, not yet operated by the respondents. Nurses in the workplace were mainly exposed to stress related to performing difficult and responsible activities. Only a small part of the respondents was definitely satisfied with their work.